Compartilhamento da informação e do conhecimento entre os bibliotecários do sistema integrado de bibliotecas da Universidade Estadual da Paraíba (SIB/UEPB). - Souza, Liliane Braga Rolim Holanda de (2016)
The sharing of information and knowledge in university libraries can be understood as a practice which can mobilize information and knowledge in order to generate new ones and organizational learning, necessary for the development of librarians activities. Thus, the objective is to analyze the share held among librarians of the “Sistema Integrado de Bibliotecas da Universidade Estadual da Paraíba (SIB/UEPB)”. As theoretical review, it is divided into two parts: an overview, converging on the area of information management and knowledge about sharing in the organizational environment with its practices, tools, influences and barriers, and; a view, focused on libraries and university librarians and their tools and sharing practices. From a methodological point of view, it is characterized, on the objectives, such as exploratory and descriptive, and the nature of the data, as quantitative qualitative. As a technique for data collection adopted the methodological triangulation, comprising: online survey, online focus groups and interviews with staff. The technique for analysis and interpretation of data was content analysis. By analyzing and interpreting the data, it was found that the share is held at the SIB / UEPB mainly informal practices, using e-mail, phone, social networking and conversations with colleagues. Librarians considered the environmental SIB / UEPB, most of the time, favorable to exchange information and knowledge. The barriers were related to geographical distance and lack of incentives. On the other hand, coordination and librarians possessed good will and interest in participating in activities that involve sharing. It is proposed an action plan for the systematic sharing among librarians of the SIB / UEPB, starting with the establishment of a responsible team and directing for the use of practices and systematic and formalized way tools.